Morphometric alterations in soy bean during drying process - Oliveira, Daniel Emanuel Cabral de; Resende, Osvaldo; Smaniotto, Thaís Adriana de Souza; Siqueira, Valdiney Cambuy; José Neto, Colemar Antônio (Semina: Ciências Agrárias, 2013)
The study aimed to evaluate the drying curves and the effects of drying temperature on the volumetric shrinkage of the grain mass and geometric diameter of the soy bean M7211RR. Were used soy bean the cultivar M7211RR harvested in Santa Helena de Goiás-GO, with an initial moisture content of approximately 0.30 d.b. (decimal dry basis) and dried to 0.13 (d.b.). The experiment was conducted at Laboratório de Pós-Colheita de Produtos Vegetais of the Instituto Federal Goiano - Câmpus Rio Verde. During the drying process, the orthogonal axes (length, width and thickness) of soy beans were measured to determine the geometric diameter. To obtain the volumetric shrinkage, the soy bean was dried on trays and then placed in graduated cylinder and thus reducing the volume of product was monitored throughout the drying. Increasing the temperature of 50 Â°C to 90 Â°C decreases the drying time of 7.66 hours to 1.98 hours, streamlining the process for 3.87 times. The rate of shrinkage and the diameter geometric of soybean decreases during drying, and this effect is intensified with increasing temperature.